Developing Halal Tourism in Ngebel Lake Ponorogo: An Analysis of DSN MUI Fatwa Number 108/DSN-MUI/X/2016 - Sodiq, Auliya Ja'far; Anggraini, Rooza Meilia (Invest Journal of Sharia & Economic Law, 2024)
This research aims to determine how to develop a Halal Tourism Area in Ngebel Lake Ponorogo in terms of DSN MUI Fatwa Number 108/DSN-MUI/X/2016. There are two discussions, namely: 1) How to implement halal tourism development in Ngebel Lake Ponorogo based on DSN-MUI Fatwa Number 108/DSN-MUI/X/2016 Guidelines for Organizing Tourism Based on Sharia Principles. 2) What is the inhibiting and supporting factors in the development of the Ngebel Lake Ponorogo tourism area based on the DSN-MUI Fatwa Number 108/DSN-MUI/X/2016 Guidelines for Organizing Tourism Based on Sharia Principles? The type of research carried out by the researchers is field research using qualitative methods. Data collection techniques included observation, interviews, and documentation. The data analysis method used by researchers is inductive. The research results show that, first, the implementation of development based on DSN-MUI Fatwa Number 108/DSN-MUI/X/2016 has not been fully carried out in accordance with the guidelines for implementing halal tourism, even though it has fulfilled several development aspects as stated in the fatwa, namely, related to the provision of tourist-friendly Muslim facilities and services. Second, the fulfillment of implementation factors in accordance with DSN-MUI Fatwa Number 108/DSN-MUI/X/2016 influenced the success factors in supporting halal tourism activities at Ngebel Lake Ponorogo. However, the non-implementation of some of the supporting factors has created an obstacle in developing halal tourism in the Ngebel Lake Ponorogo area because it has not been implemented, as stated in the implementation guidelines according to Fatwa.